Identifying the mastery of research statistical concept by using problem-based learning - Susbiyanto Susbiyanto; Dwi Agus Kurniawan; Rahmat Perdana; Cicyn Riantoni (International Journal of Evaluation and Research in Education (IJERE), 2019)
The consequence of the assessment for the research statistics course at the department of physics Education in Universitas Jambi demonstrates the students' capacities to hold the idea of the mastery of research statistical concept is very low. It winds up one of the shortcomings for them to finish their final assignment. Therefore, the researcher examined the student's mastery of the research statistical concept by utilizing Problem-Based Learning as one of the methods that were chosen from the learning advancement. The research method is quantitative with 295 numbers of samples. Questionnaires and MCQs were used as the instruments of the research. The result had been investigated utilizing a simple regression analysis. PBL influences the mastery of research statistical concept. In 6th semester male students', the impact of PBL toward the mastery of the research statistical concept contributed 72% and 67% for female students. Meanwhile, for students at 8th semesters, the impact of PBL on the mastery of research statistical concept contributed 68% for male and 70% for female.